1995
DOI: 10.1111/j.1365-4362.1995.tb04382.x
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Reduces Recurrences of Basal Cell and Squamous Cell Cancers

Abstract: Interferon treatment makes it possible to achieve a persistent cure in patients with BCC and SCC in a high proportion of cases. The potential advantage of nonsurgical treatment are an enhancement of cosmetic results through the prevention of destruction of important anatomic structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 9 publications
0
11
0
1
Order By: Relevance
“…Kuflik et al 16 reported a 5-year cure rate of 96% for SCC achieved by cryosurgery. Ikic et al 17 demonstrated that the interferon treatment can produce a persistent cure (5 years) in patients with SCC (recurrence rate, 4%). A complete response rate of 63% was achieved with topical PDT in superficial SCC on face, scalp, or neck.…”
Section: Discussionmentioning
confidence: 97%
“…Kuflik et al 16 reported a 5-year cure rate of 96% for SCC achieved by cryosurgery. Ikic et al 17 demonstrated that the interferon treatment can produce a persistent cure (5 years) in patients with SCC (recurrence rate, 4%). A complete response rate of 63% was achieved with topical PDT in superficial SCC on face, scalp, or neck.…”
Section: Discussionmentioning
confidence: 97%
“…Some preliminary evidence suggests that vitamin supplementation may reduce the risk of basal cell carcinoma28 and that interferon reduces recurrence. 29 Further studies are required to confirm these observations. The choice of treatment depends on the size and site of tumour, age of patient, efficacy of treatment modality, cosmetic considerations, and the preferences of patient and physician.…”
Section: Predisposing Factorsmentioning
confidence: 96%
“…Kuflik and Gage 10 reported a 5-year cure rate of 99% for BCC and 96% for SCC achieved by cryosurgery. Ikic et al 20 demonstrated that interferon treatment can produce a persistent cure (5 years) in patients with *The lesions were treated with different wave bands of light, including fullspectrum visible light, filtered visible light ( Ͼ515, Ͼ570, or Ͼ610 nm), and UV-A, as specified in the "Patients, Materials, and Methods" section. There was no statistically significant difference among the clinical response rates of basal cell carcinoma and squamous cell carcinoma to the different wave bands of light.…”
Section: Commentmentioning
confidence: 99%